Synergizing Growth Mindset and Generative AI in K-12 Classrooms: A Framework for Fostering Resilient Learners in an Era of Uncertainty - M. Afan Gaffar; Muhammad Zaki Aulawy; Wahyu Cahyana; Irvan Budhi Handaka; Ega Asnatasia Maharani (The Indonesian Institute of Science and Technology Research, 2026)
The rapid proliferation of generative artificial intelligence (GenAI) in educational settings presents both unprecedented opportunities and significant challenges for K-12 educators. This conceptual article examines the intersection of growth mindset pedagogy and GenAI integration in classroom learning environments. Drawing upon self-determination theory (SDT) and control-value theory (CVT), this paper proposes an integrated framework positioning teacher support as the critical mechanism through which students develop adaptive beliefs about intelligence while learning to collaborate with AI tools. The article synthesizes recent empirical evidence from 49 studies examining GenAI's impact on student learning, K-12 systematic reviews, and research on psychological needs satisfaction in technology-mediated contexts. Findings are organized into three thematic areas: (1) the dual nature of GenAI as both scaffold and potential crutch for learner development; (2) teacher strategies for cultivating growth-oriented AI literacy; and (3) classroom structures that support autonomy, competence, and relatedness in AI-integrated lessons. The proposed Growth Mindset-AI Synergy Framework offers practical guidance for educators seeking to harness AI's potential while preserving the essential human elements of teaching—empathy, mentorship, and belief in student potential. The article concludes that the deliberate cultivation of growth mindsets, supported by strategic teacher intervention, enables students to view AI not as a shortcut to accomplish a task, but as a cognitive partner in their ongoing intellectual development.